Poverty In West Sulawesi; Analysis Of Education Level And Investment Through Economic Growth - Baso Iwang; Afiq Nazrin Rizlan; Irfandi T (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2023)
Poverty and Economic Growth are important indicators in achieving the success of a country's development. To achieve development, each country and region will try to optimize economic growth and reduce poverty. This study aims to determine the effect of the level of education and investment on poverty through economic growth in West Sulawesi Province. The data used by the authors in this study are secondary data of the time series type from 2012 to 2021 obtained from the West Sulawesi Central Bureau of Statistics. In this study also used quantitative research, using the path analysis method. The results of this study indicate that the level of education has a positive and significant effect on economic growth. While investment has a positive and insignificant effect on economic growth. The level of education and economic growth have a positive but not significant effect on poverty in West Sulawesi Province. Meanwhile, investment has a positive and significant impact on poverty in West Sulawesi Province. The level of education and investment has a negative and not significant indirect effect on poverty through economic growth in West Sulawesi Province. Policy implication of this research are need for better handling related to the allocation of investment both domestic and foreign to encourage economic growth in an effort to reduce poverty in West Sulawesi Province. Efforts are needed to increase and equalize investment in all areas of West Sulawesi Province.